LC-MS/MS study of in vivo fate of hyaluronan polymeric micelles carrying doxorubicin - Šimek, Matěj; Hermannová, Martina; Šmejkalová, Daniela; Foglová, Tereza; Souček, Karel; Binó, Lucia; Velebný, Vladimír (Carbohydrate polymers, 2019)
A better understanding of in vivo behavior of nanocarriers is necessary for further improvement in their development. Here we present a novel approach, where both the matrix and the drug can be analyzed by LCMS/MS after one sample handling. The developed method was applied for the comparison of pharmacokinetic profile of free and encapsulated doxorubicin (DOX) in oleyl hyaluronan (HA-C18:1) polymeric micelles. The results indicated that nanocarriers were rapidly dissociated upon in vivo administration. Despite this fact, the administration of encapsulated DOX led to its longer circulation time and enhanced tumor targeting. This effect was not observed injecting blank HA-C18:1 micelles followed by unencapsulated DOX. Biodistribution studies and molecular weight estimation of the carrier matrix indicated relatively high stability of HA-C18:1 ester bond in bloodstream and complete elimination of the derivative within 72 h. The proposed methodology provides a novel strategy to elucidate the pharmacokinetic behavior of polysaccharide-based drug delivery systems.
Keywords: nosiče léků; Hyaluronan; Molecular Weight; Drug Carriers; Tissue Distribution; Doxorubicin; molekulová hmotnost; micely; Mice; kyselina hyaluronová; doxorubicin; ženské pohlaví; zvířata; tkáňová distribuce; Polymeric micelles; Hyaluronic Acid; Tandem Mass Spectrometry; Biodistribution; Drug Liberation; chromatografie kapalinová; uvolňování léčiv; Micelles; myši; tandemová hmotnostní spektrometrie; Pharmacokinetics; Chromatography, Liquid; Female; Animals